Garantismo Penal para Quem? O Discurso Penal Liberal Frente à sua Desconstrução pela Criminologia - Freitas, Marisa Helena D´arbo Alves De; Mandarino, Renan Posella; Rosa, Larissa (Programa de Pós-Graduação em Direito da Universidade Federal de Santa Catarina, 2017)
Abstract The present article deals with the effectiveness of individual guarantees and the reflection of this problem in access to brazilian criminal justice. In spite of the guarantees speech present the possible instruments for the defense of the accused and to equality of treatment to subjects in the process, the reality procedure indicates that this discourse is merely rhetorical and limited to theoretical plane-abstract, with difficulties to achieve practical-reformist. The work is bibliographic and develops concepts concerning the selectivity and the ways of controlling punitive power. To approach the subject, it was assumed the critical perspective of penal guaranteeism proposed by Luigi Ferrajoli.

Resumo O presente artigo versa sobre a efetividade das garantias individuais e o reflexo dessa problemática no acesso à justiça penal brasileira. Apesar de o discurso garantista apresentar os instrumentos possíveis para defesa dos acusados e para isonomia de tratamento aos sujeitos do processo, a realidade processual indica que esse discurso é meramente retórico e limitado ao plano teórico-abstrato, com dificuldades de se concretizar no plano prático-reformista. O trabalho é bibliográfico e desenvolve conceitos relativos à seletividade e às formas de controle do poder punitivo. Para abordagem do tema, partiu-se da perspectiva crítica do garantismo penal proposto por Luigi Ferrajoli.
Criminal Guarantees for Whom? The Speech Liberal Criminal Front to this Deconstruction by Criminology
Keywords: Criminal Guarantees; Selectivity; Critical Criminology.; Garantismo Penal; Seletividade; Criminologia Crítica